EVALUATION OF NEONATAL RESPIRATORY SUPPORT OUTCOMES IN LOCAL POPULATION: FROM SURFACTANT THERAPY TO HIGH-FREQUENCY VENTILATION – A RETROSPECTIVE COHORT STUDY - KHAN , M; ALI , H; AZMATULLAH , M; DIN , N (Biological and Clinical Sciences Research Journal, 2024)
Neonatal respiratory distress syndrome (RDS) is a leading cause of neonatal mortality in Pakistan. Surfactant therapy and high-frequency ventilation (HFV) have been pivotal in improving survival rates. This study aims to evaluate the clinical outcomes of newborns with RDS treated with surfactant therapy and HFV in Pakistani tertiary care centres. Objective: To assess the impact of surfactant therapy and HFV on neonatal mortality, incidence of bronchopulmonary dysplasia (BPD), length of NICU stay, and overall survival rates in neonates with RDS. Methods: A retrospective cohort study was conducted at Swat Medical College, Swat, Pakistan in the duration from October 2023 to March 2024. Data were collected on neonates diagnosed with RDS, with two treatment groups: those receiving surfactant therapy only (Group A) and those receiving surfactant therapy with high-frequency ventilation (Group B). Statistical analysis was conducted using SPSS 25.0, comparing mortality rates, BPD incidence, and length of NICU stay between the two groups. Results: Among 300 neonates included in the study, Group A (n=150) had a neonatal mortality rate of 25%, while Group B (n=150) had a mortality rate of 15% (p=0.02). The incidence of BPD was significantly lower in Group B (18%) compared to Group A (30%) (p=0.03). The median length of NICU stay was 20 days for Group A and 15 days for Group B (p=0.01). Neonates receiving HFV had better overall survival outcomes. Conclusion: The use of HFV, combined with surfactant therapy, significantly improves survival outcomes and reduces BPD incidence and NICU stay duration in neonates with RDS.